Pengoptimalan Akuntanbilitas Tanggung Jawab Sosial dan Lingkungan (TJSL) pada Perusahaan Tambang di Indonesia - Reza Hening Wijaya; Utpala Rani; Nibras Anny Khabibah (Wahana Riset Akuntansi, 2020)
This descriptive research aims to depict the extent to which mining companies in Indonesia are trying to be accountable for the implementation of social and environmental responsibility. The identification results of 15 coal mining companies’ annual reports of show that most companies rely on qualitative explanations to provide confidence to stakeholders about their behavior towards the environment and society. The lack of companies that disclose quantitative aspects and the relevance of social and environmental responsibility activities can indicate a lack of seriousness by the company in realizing its promise to preserve nature and improve the lives of the surrounding communities Keywords: Green Accounting; CSR; Accountability; Coal Mining Corporations